Characterization of Hepatitis B Virus Transcripts in Chronically HBV-Infected Chimpanzees and Patients Treated with ARC-520 siRNA Demonstrates Transcriptional Silencing of cccDNA - Christine I. Wooddell; Dean Sanders; Zhao Xu; Lung-Yi Mak; Thomas Schluep; Wai-Kay Seto; Bruce D. Given; Man-Fung Yuen (Viruses)
Full-length hepatitis B virus (HBV) transcripts of chimpanzees and patients treated with multidose (MD) HBV siRNA ARC-520 and entecavir (ETV) were characterized by single-molecule real-time (SMRT) sequencing, identifying multiple types of transcripts with the potential to encode HBx, HBsAg, HBeAg, core, and polymerase, as well as transcripts likely to be derived from dimers of dslDNA, and these differed between HBeAg-positive (HBeAg+) and HBeAg-negative (HBeAg−) individuals. HBV transcripts from the last follow-up ~30 months post-ARC-520 treatment were categorized from one HBeAg+ (one of two previously highly viremic patients that became HBeAg− upon treatment and had greatly reduced cccDNA products) and four HBeAg− patients. The previously HBeAg+ patient received a biopsy that revealed that he had 3.4 copies/cell cccDNA (two to three orders of magnitude more cccDNA than HBeAg− chimpanzees) but expressed primarily truncated X and HBsAg from iDNA, like two patients that were HBeAg− at the start of the study and had one copy/cell cccDNA. No HBV transcripts were detected in two other HBeAg− patients that had ~0.3 copies/cell cccDNA, one of which had seroconverted for HBsAg. The paucity of cccDNA-derived transcripts in the presence of high cccDNA demonstrates the transcriptional silencing of HBV following MD siRNA treatment with ETV.